Trading Patterns and Market Integration in Overlapping Experimental Asset Markets - Chelley-Steeley, Patricia; Kluger, Brian; Steeley, James; Adams, Paul (Journal of Financial and Quantitative Analysis, 2015)
Abstract This paper examines trading patterns and market integration using laboratory asset markets. Our markets are designed to approximately correspond to the trading day for stocks cross-listed in markets in Europe and North America. Some of our markets feature timing restrictions so that participants cannot trade across markets except during a fully integrated overlap period. Comparison of markets with and without timing restrictions shows that restrictions reduce trading activity and shift transactions to the overlap period. When asset values are extreme, price discovery can be impeded when trading restrictions exist. The measurement of liquidity suggests that trading restrictions increase overall spreads.